Post-ganglionic Horner's syndrome: An unusual presentation of non-Hodgkin lymphoma - Resende, Lucilene Silva Ruiz e [UNESP]; Gaiolla, Rafael Dezen; Niéro-Melo, Ligia [UNESP]; Domingues, Maria Aparecida Custódio [UNESP]; Resende, Luiz Antonio de Lima [UNESP] (Karger Publishers, 2012)
In this paper, we present the rare case of a patient with cervical lymphadenopathy diagnosed as a T-cell-rich B-cell non-Hodgkin lymphoma that manifested Horner's syndrome due to a post-ganglionic sympathetic neuron lesion caused by the tumor. Copyright © 2012 S. Karger AG, Basel.
Keywords: Cervical lymphadenopathy; Horner's syndrome; Neoplasia; Non-Hodgkin lymphoma; Third-order neuron pathway; carboplatin; etoposide; ifosfamide; adult; autologous bone marrow transplantation; cancer combination chemotherapy; cancer regression; cancer relapse; cancer staging; case report; cervical lymphadenopathy; computer assisted tomography; female; Horner syndrome; human; immunohistochemistry; nonhodgkin lymphoma; postganglionic nerve; priority journal; salvage therapy; sympathetic innervation; T cell rich B cell non hodgkin lymphoma; tumor biopsy